2012
DOI: 10.5539/ijb.v4n2p112
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients Impact on Soybean (Glycine max (Merrill)) Qualitative and Quantitative Traits

Abstract: In order to study the effects of applying the micronutrients zinc, manganese, and boron, and to compare the effects that incorporating them in the soil and spraying them on the crop on seed oil and protein contents and percentages, a study was conducted based on the factorial design with the two factors of incorporating these micronutrients in the soil and spraying them on the crop, in 16 treatments and four replications (a total of 64 trials), in 2009-2010 in Dasht-e-Naz in Sari of northern Iran. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
3
4
1
Order By: Relevance
“…Hellal and Abdelhamid (2013) reported that total manganese uptake by the soybean plants per metric ton of grain production is 123 g. Manganese fertilization increased oil content in soybean grain, but this increased was not statistically significant. These results are in contrast with the results obtained by Yasari and Vahedi (2012) that showed the highest seed oil yield in soybean was obtained by applying manganese. Economic yield ranged between 2305.83-1627.50 kg haG 1 in cultivars.…”
Section: Resultscontrasting
confidence: 99%
“…Hellal and Abdelhamid (2013) reported that total manganese uptake by the soybean plants per metric ton of grain production is 123 g. Manganese fertilization increased oil content in soybean grain, but this increased was not statistically significant. These results are in contrast with the results obtained by Yasari and Vahedi (2012) that showed the highest seed oil yield in soybean was obtained by applying manganese. Economic yield ranged between 2305.83-1627.50 kg haG 1 in cultivars.…”
Section: Resultscontrasting
confidence: 99%
“…Pod number is considered to be the major yield determinant in pigeonpea, foliar spray of N, P and K through all nineteen was able to increase the pod number in this experiment. These results are in conformity with the earlier findings of with Yasari et al [6].…”
Section: Effect Of Foliar Nutrition On Yield Parameters Of Pigeonpeasupporting
confidence: 94%
“…This would be due to the foliar application of higher concentration of multinutrients at critical growth stages which increased the growth and yield parameters. These results are in confirmity with the earlier findings of with Yakadri et al, 2002 andYasari et al, 2012.…”
Section: Number Of Pods Per Plantsupporting
confidence: 93%